2018
DOI: 10.1093/ser/mwy003
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating the market: moral exchange and the sharing economy

Abstract: The ‘sharing economy’ is a contested realm, with critics arguing it represents a further development of neoliberalism, as platforms such as Airbnb and TaskRabbit, monetize previously uncommodified realms of life via renting of bedrooms, possessions, space and labor time. To date, this debate has largely ignored participants’ views. Using data from 120 in-depth interviews with providers in two for-profit and three not-for-profit sites, we find that most see the sharing economy differently, as an opportunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 45 publications
1
54
0
4
Order By: Relevance
“…The findings of the research are consistent with the remarks and conclusions of prior studies on the topic, including the following: Prothero et al (), Sacks (), and Böcker and Meelen () with regard to sustainability concerns; Botsman and Rogers (), Tussyadiah (), Martin (), Fitzmaurice et al (), and Frenken and Schor () with respect to social and socializing benefits; Hamari et al (), Bellotti et al (), Möhlmann (), and Cherry and Pidgeon () with regard to economic benefits; and Heinrichs (), Owyang et al (), and Vătămănescu and Pînzaru () with respect to approaches to the role of knowledge in sharing contexts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings of the research are consistent with the remarks and conclusions of prior studies on the topic, including the following: Prothero et al (), Sacks (), and Böcker and Meelen () with regard to sustainability concerns; Botsman and Rogers (), Tussyadiah (), Martin (), Fitzmaurice et al (), and Frenken and Schor () with respect to social and socializing benefits; Hamari et al (), Bellotti et al (), Möhlmann (), and Cherry and Pidgeon () with regard to economic benefits; and Heinrichs (), Owyang et al (), and Vătămănescu and Pînzaru () with respect to approaches to the role of knowledge in sharing contexts.…”
Section: Discussionsupporting
confidence: 87%
“…The motivational drivers linked to social benefits and, thus, to socializing have been consistently addressed by Botsman and Rogers () and Tussyadiah (), whose findings reveal the influence of social incentives on participation. Within this framework, Botsman and Rogers identify the opportunity to meet peers and to make new friends among the key drivers of participation in the sharing market (Fitzmaurice et al, ; Martin, ). Here, Frenken and Schor () underscore that “to the extent that sharing peers also create meaningful contacts, sharing practices increase social mixing” (p. 6).…”
Section: Literature Review the Research Model And Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the social benefits, there is a widespread "common good" claim by a number of platforms, as well as participants on both sides of the market which is the benefit of meeting people, making friends and getting to know others (Fitzmaurice et al 2018). Schor (2015a) finds that the site that has been most successful at creating new social ties is Airbnb.…”
Section: Assessing the Sharing Economymentioning
confidence: 99%
“…Participants on other sites also note the importance of social ties. Schor (2015a) and Fitzmaurice et al (2018) found that TaskRabbits say the platform helped them build new social networks they can rely on and afforded the opportunity to meet people they would have never met. They report satisfaction with the relations they developed with the people they do tasks for.…”
Section: Assessing the Sharing Economymentioning
confidence: 99%